Modifikasi Materi Pratikum (Karbohidrat-Enzim) untuk Meningkatkan Pemahaman Konsep Biokimia Secara Komprehensif dan Efisien - Titik Wijayanti; Purwaning Budi Lestari (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2016)
Main objectives of this research are to analysis the increase in understanding biochemistry conceptscomprehensively caused by practice concept modification (Carbohydate-Enzyme) and analysis the efficiencyof practical activities caused by practice concept modification (Carbohydate-Enzyme). Research conducted inSeptember through November 2015 are analytical descriptive research, there are 80 students as respondentswere devided into 2 groups of treatment, namely group A as group with practice module that has not beenmodified and group B with practice module that have been modified. Paired t test result showed that groupwith practice module were modified to get the score of post-test evaluation better and significantly differentthan group with practice module that has not been modified. The validation result of practice module bystudents, instucture, material experts and media experts showed that practice module modified is eligible toused as practical module in the future.